Enhanced Robotic Systems in Minimally Invasive Surgery - Mohammad Taleb Khudair Abbas; Kamal Al-din hashim ali hashim; Hussein Mohammed Sahib Hamid; Asmaa Munther Saleh Awaid (American Journal of Botany and Bioengineering, 2024)
Minimally invasive surgery has been evolving rapidly since the beginning of the nineties, mainly due to the advent and continuous implementation of robotic systems. This paper reviews the main advancements achieved with the use of robotics by focusing on recently proposed and developing robotic systems specifically designed for minimally invasive surgery, indicating how the evolution of robotics is progressing. All the improvements offered by robotic systems are discussed in detail, beginning with the flexibility in the architecture of the last decade, which was tailored to accommodate instruments and manipulators for general minimal access surgery. The introduction of mechatronic wrists was one of the initial steps toward the development of intelligent systems recently proposed to offer haptic/tactile feedback and improve the performance of interventions in the presence of non-rigid organs. After an overview of individual proposals and studies of the benefits of robotic systems in surgery in terms of accuracy, proactivity, and trauma, new actuation technologies are discussed, enabling developments in exoscopy and endoscopy in ergonomics to aid smooth operation in complex environments. Minimally invasive surgery has become increasingly prominent in the operating room in recent decades, offering a series of advantages for surgeons, surgeons-in-training, and patients in comparison to open surgery. The most notable of such advantages is the reduction in surgical trauma and the related complications, including pain, scarring, and the need for analgesic drugs. This corresponds to a reduction in hospital stay and an increase in the successful outcome of surgeries while greatly reducing both visible and invisible scarring. In order to further improve the advantages of minimally invasive surgery and better aid both the surgeon and the patient, the use of surgical robotic systems has become increasingly popular in the medical field. [1][2][3]